(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article says that each country has its own traditional knowledge that requires legal protection. In this regard, there is a need to develop mechanisms for the implementation of an international regime for the protection of such knowledge, genetic resources and knowledge related to resources.